Analisis Perusahaan PT Garuda Food Putra Putri Jaya Tbk - Amelia Brata Anglara Putri (Jurnal Syntax Admiration, 2024)
This study aims to analyze the company's strategy of PT Garuda Food Putra Putri Jaya Tbk in facing the dynamics of the food and beverage industry in Indonesia. Using matrix analysis methods such as SPACE, BCG, IE, and Grand Strategy Matrix, the study found that companies implement aggressive strategies that take advantage of internal strengths such as product diversification and extensive distribution networks. In addition, the company is also taking advantage of the industry's growth and increasing consumer awareness of health. The results of the study also show the importance of risk management faced by companies. Strategy recommendations include vertical integration, market development, and product development, in order to strengthen the company's position and achieve sustainable growth in a competitive market.